Development of human hand phantom containing radiophotoluminescence material. (February 2016) - Sato, Fuminobu; Maekawa, Tatsuro; Sakiyama, Tomoki; Zushi, Naoki; Shimizu, Kikuo; Kato, Yushi; Murata, Isao; Yamamoto, Takayoshi; Iida, Toshiyuki
Abstract: A radiophotoluminescence (RPL) material with high radiation sensitivity was made of polyurethane resin, silver-activated metaphosphate glass particles, and hollow glass microspheres. The density was adjusted to be 1.1 g/cm 3 by controlling the amount of hollow glass microspheres. The response to high-energy photons over 100 keV was similar to that of the tissue-equivalent material (polymethylmethacrylate) because the two electron densities were similar. The RPL response had satisfactory linearity in the dose range from 10 to 6 × 10 4  mGy. An RPL scanner for three-dimensional (3-D) dose measurement was composed of an XYZθ motorized stage, a UV pulse laser, a gated photomultiplier tube (PMT), a red-laser displacement sensor, and an integrating ammeter. The surface profile was measured by the red-laser-displacement sensor. The UV laser was used as an excitation source, and the RPL responses were effectively detected with the gated PMT. An RPL material hand phantom was fabricated to understand the extremity dosimetry of a radiation worker's hand. The hand phantom was exposed to X-rays, and its surface dose profile was obtained by the RPL scanner. Subsequently, the hand phantom was sliced into dozens of square plates using a diamond wire saw. Each inner dose profile was obtained with the RPL scanner. The inner dose profiles were roughly consistent with the computational simulation results. These results indicated that RPL imaging of the hand phantom was useful to understand extremity dosimetry. Highlights: We developed a highly radiation-sensitive radiophotoluminescence (RPL) material. An RPL material hand phantom was fabricated to understand extremity dosimetry. The 3-D dose distribution in the hand phantom was obtained by RPL imaging.